Interoperability in pedagogical e-learning services - Queirós, Ricardo (2009)
The ultimate goal of this research plan is to improve the learning experience of students through the combination of pedagogical eLearning services. Service oriented architectures are already being used in eLearning but in this work the focus is on services of pedagogical value, rather then on generic services adapted from other business systems. This approach to the architecture of eLearning platforms raises challenges addressed by this work, namely: conceptual modeling of the pedagogical eLearning services domain; interoperability and coordination of pedagogical eLearning service; conversion of existing eLearning systems to pedagogical services; adaptation of eLearning services to individual learners. An improved eLearning platform will incorporate learning tools adequate to the domains it covers and will focus on the individual learner that uses it. With this approach we expect to raise the pedagogical value of eLearning platforms.